Serviços ecossistêmicos na bacia hidrográfica de um reservatóriohidrelétrico em cenário de escassez de água - Carolina Rezende Savino Silveira (2016)
Ecosystem services are natural processes that ensure the survival of species on the planet and to offer goods and services that satisfy human needs. The purpose of this Master dissertation was to identify the variables that contribute most to the ecosystem service of erosion control and siltation, as well as to characterize the ecological conditions of theriver in the Nova Ponte Hydropower Plant (NPHP).The hypothesis was that in sub-basins with riparian zone occurs less sediment transport; while in those degraded riparian zona higher sediment transport occurs. Three groups of variables were evaluated: (i) the land use and soil occupation, (ii) geomorphology and (iii) metrics of physical habitats related to the morphology of the channel, types of sediment, riparian vegetation cover and human impacts. All these data were analyzed by comparing the results obtained in 2009 and 2013. This comparison allowed the evaluation of two different scenarios regarding wateravailability, since 2009/2010 was a period of regular average rainfall, while 2013/2014 there was a lack of rain. Based on human activities and environmental characteristics of the headwater streams on the NPHP Environmental Fragility maps were constructed, featuring streams as their conservation status. The physical habitat metrics were calculated after applying Protocol of Physical Habitat by the US Environmental Protection Agency in 40 headwater streams upstream of the Nova Ponte Reservoir. The results demonstrate that the watershed of the UHE Nova Ponte presents considerable urbanized, with half of the area isoccupied by agricultural activities. The region has the dominant geology schist (metamorphic rock susceptible to erosion), being predominantly made up of schist. Through the Environmental Fragility Maps it is shown that some improvements for the conservation status were applied after four years due to the percentage increase in the riparian vegetation canopy in the streams. Only the variable "forest" was significantlyrelated to the stability of the bed (p <0.05) when comparing the two sampling periods (em 2009, R2 = 0,42; = 0,30; p < 0,05 e em 2013, R2 = 0,11; = 0,40; p < 0,05). Obtained results confirm the importance of conservation of riparian forests for the maintenance of ecosystem service of erosion control and siltation, besides contributing to maintenance ofthe water cycles and recharge of aquifers and consequent maintenance water levels of hydropower reservatories. Considering the current scenario of drought, investiments in the restoration of riparian zone are essencial to ensure the continuity of the range of ecosystem services they offered.